Status of Sandalwood (Santalum album Linn.) in Low Hills of Himachal Pradesh - Dutt, Som; Sharma, Kamal; Sharma, Vivek; Dhiman, Varun (International Journal of Economic Plants, 2021)
The present investigation on the status of Sandalwood (Santalum album Linn.) in low hills of Himachal Pradesh was carried out in the Department of Silviculture and Agroforestry in the laboratory at the main campus of the Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan and in the field at Bilaspur and Jawala Mukhi varying in altitude from 500–850 m. The growth behavior of sandals was studied through the selection of 10 ha sampling plot at Bilaspur and 5 ha sampling plot at Jawala Mukhi based on tree density. The investigations revealed that the trees have covered an area of 15 ha at Bilaspur and 30 ha at Jawala Mukhi. The total number of trees growing at Bilaspur and Jawala Mukhi was found to be 1076 and 815, respectively. Further, average oil content was about 3.86 and 3.90% in the heartwood of S. album growing at Bilaspur and Jawala Mukhi. Phytosociological parameters of vegetation in sandal stand at Bilaspur revealed Santalum album as the dominant tree species with its maximum IVI value which corresponds to its higher frequency, basal area, and density.